Polyphenoloxidase from Starfruit (Averrhoa carambola, L.) I - Tengku Adnan, Tengku Adnin; Augustin, M. A.; Mohd Ghazali, Hasanah (1986)
Polyphenoloxidase (PPO) was z50lated from starfruit (Averrhoa carambola, L.) and purified by acetone precipitation and dialysis. The optimum pH for the aCl}tone purified PPO catalysed oxidation of catechol was found to be pH 7.2 Heat 'inactivation studies showed that the enzyme was heat-labile. Haif-Hvesfor PPO 'inactiivation at 70°C and 75°C were found to be 4.6 min and 3.1 min respectively. The Michaeline constant (K j and V for catechol with PPO was O. 061M and 20 U ml-1 respectively.